Pemberdayaan Masyarakat Desa Sari Makmur secara Berkelanjutan melalui Pengembangan Keterampilan dan Inovasi UMKM - Liani, Liani; Hendri, M. Irfani; Dahlia, Dahlia; Ananda, Intan Cahya Ananda; Vera, Alensia Anjelika; Natalia, Natalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Independence of the nation's economy is relying on empowerment of the rural economy based on its potential. This empowerment is crucial for fostering sustainable growth, as rural areas often hold untapped resources and opportunities for development that can lead to overall economic stability. However, some rural areas including Sari Makmur Village might face some challenges that hinder their progress. Limited access to education, inadequate infrastructure, and insufficient investment in local businesses creates some barriers that could prevent Sari Makmur Village from reaching its full potential. Addressing these issues by improving education through interactive methods, job preparation workshop, financial literacy until MSMEs empowerment allows Sari Makmur Village to contribute meaningfully to the national economy.